Meningkatkan Pengetahuan dan Kesadaran Masyarakat Khususnya Orang Tua Mengenai Kekerasan Seksual dalam Rangka Pencegahanan Terjadinya Tindakan Kekerasan Seksual di Kecamatan Pauh Kota Padang - Fachrina Fachrina; Aziwarti Aziwarti; Machdaliza Machdaliza; Zeni Eka Putri; Damsar Damsar (Warta Pengabdian Andalas, 2019)
Although acts of sexual violence are rife and have become a national issue, at the community level, this can be said to be relatively un holistically socialized. The community, especially parents who have children, should get complete, correct and accurate information on matters relating to sexual violence, given the data that the perpetrators tend to be the closest people who still have family relations such as brothers, uncles and even their own fathers. In addition to providing knowledge and understanding of sexual violence and prevention efforts, the purpose of this activity was also to encourage the community, especially parents, to become empowered and responsible figures for the safety of children to avoid acts of sexual violence. The method used of implementing activities through lectures or counseling for adult learning and Focus Group Discussion (FGD).